Effect of Liraglutide combined with Jinlida granules on glycolipid metabolism and islet function of type 2 diabetes mellitus: Liraglutide combined with Jinlida granules in T2DM - Wang, Xianjuan; He, Kun; Li, Jing; Liu, Ying; Peng, Zhaokang; Zhao, Lijuan; Ji, Shumin (Cellular and Molecular Biology, 2024)
To investigate whether Liraglutide combined with Jinlida granules affects glycolipid metabolism and islet function in the treatment of type 2 diabetes mellitus (T2DM), a control group and an observation group were established with 90 T2DM patients. The control group was given Jinlida treatment and the observation group was given liraglutide combined treatment for 12 weeks. The clinical efficacy, glycolipid metabolism, bone metabolism, islet function, and endothelial function. The curative effect of the observation group was better than that of the control group. After treatment, FBG, 2hPG, HbAlc, TC, TG, and LDL-C in the observation group were lower and HDL-C was higher than those in the control group (P < 0.05). After treatment, the observation group showed higher bone mineral density, osteocalcin, FINS, and HOMA-β and lower HOMA-IR than the control group (P < 0.05). After treatment, endothelin-1 level in the observation group was lower than that in the control group, and the NO level was higher (P < 0.05). No significant difference was found in the incidence of adverse reactions between the two groups (P > 0.05). Liraglutide combined with Jinlida in T2DM can improve glucose, lipid, and bone metabolism, promote the recovery of islet function, and enhance vascular endothelial function.